The Relationship between Th1/Th2 Balance and 1?, 25-Dihydroxyvitamin D3 in Patients with Allergic Rhinitis - Keles, Erol; Ozkara, Sule; Ilhan, Nevin; Gungor, Hilal; Karlidag, Turgut; Yalcin, Sinasi (Galenos Yayincilik, 2015)
Objective: With regard to the correlation between T helper1/T helper2 (Th1/Th2) cell balance and 1 alpha, 25-dihydroxyvitamin D-3, active metabolite of vitamin D, we studied Th1/Th2 cell balance by measuring levels of the cytokines interleukin (IL)-4, IL-10 and interferon-gamma (IFN-gamma), which are important for immune response of patients with allergic rhinitis. Methods: Thirty adult patients diagnosed with allergic rhinitis (study group) and 40 healthy volunteers (control group) are examined in the research. IFN-gamma, IL-4, IL-10, and total immunoglobulin E (IgE) levels from serum samples and vitamin D-3 levels from plasma were determined in all patients. Results: In IgE, IL-4, IL-10, IFN-gamma, and 1 alpha, 25-dihydroxyvitamin D-3 levels (p< 0.05), a statistically noticeable difference was observed between the study and control group. The 1 alpha, 25-dihydroxyvitamin D-3 levels in both groups were compared and a statistically significant difference between the 1 alpha, 25-dihydroxyvitamin D-3 levels in the study group and that in the control group (p< 0.05) was observed. There was a positive correlation between IFN-gamma and vitamin D levels (p< 0.05) in the study group, whereas IgE, IL-4, and IL-10 levels showed a negative correlation with vitamin D-3 levels (p< 0.05). Conclusion: In our study, 1 alpha, 25-dihydroxyvitamin D-3 levels were associated with Th1/Th2 balance in allergic rhinitis, and a remarkable correlation was observed among vitamin D deficiency and allergy. These findings show that 1 alpha, 25-dihydroxyvitamin D-3 may have a remarkable role in the severity and control of allergic disorders. In addition, further investigations are required to confirm how vitamin D should be used in allergic diseases. Furthermore, to reveal the exact mechanism of vitamin D on allergic diseases, further studies are required.
Keywords: Rhinitis; allergic; cholecalciferol; Th1 cells; Th2 cells; interleukin-4; interleukin-10; interferon-gamma